Polityka Platformy Obywatelskiej wobec wymiaru sprawiedliwości - Kopciuch, Krzysztof (Polityka i Społeczeństwo, 2021)
This article presents an analysis of the Civic Platform’s political program in relation to the demands on the judiciary. After initially showing the origins of the party, the program analyzes the programming document “Commitment” in 2001 and the program of election campaigns from 2005. The article contains an analysis of the political program of the party prior to the election victories in 2007 and 2011 taking into account political achievements in this matter